Zn-deficient states in human erythrocytes in vitro and free radical processes - Harmaza, Yuliya M.; Tamashevski, Alexander V. (Journal of the Belarusian State University. Ecology, 2018)
It was established that incubation of human erythrocytes with an intracellular chelator N’,N’-tetrakis(2-methyl-pyridyl)ethylenediamine (TPEN) in subhemolytic concentrations leads to a significant decrease in the Zn2+ intracellular pool and cells esterase activity rise. It was demonstrated that one of the possible mechanisms of an oxidative stress development in zinc deficient human erythrocytes is the inhibition of the main antioxidant enzymes activity – catalase and glutathione peroxidase as well as changes in the reduced glutathione concentration. It was found that decreased glutathione peroxidase activity exactly contributes to the erythrocyte esterases activation under zinc ions deficiency. An increased expression of the cysteine-rich proteins metallothioneins in human erythrocytes under simulation of the Zn-deficient state in vitro was revealed. It confirms the hypothesis about the functioning of these proteins as an auxiliary antioxidant in a protective cell system.